Implementasi Maqasid Syariah dalam Kebijakan Program Makan Bergizi Gratis (MBG) di Indonesia - Muhammad Hamim Arriza (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
This study examines the implementation of the maqasid sharia principles in the Free Nutritional Meals (MBG) policy in Indonesia, a government program aimed at improving the quality of health and education by providing nutritious meals for students. Despite its noble objectives, numerous cases of mass poisoning have demonstrated weaknesses in governance and quality control, raising questions regarding its compliance with Islamic ethical principles, particularly the protection of the soul (ḥifẓ al-nafs) and the protection of the mind (ḥifẓ al-‘aql). Previous studies have focused primarily on the socio-economic impacts of the MBG, but few have examined it from an Islamic public policy perspective, creating a research gap that needs to be filled. This study employed qualitative methods with a library research approach and content analysis of policy documents, fatwas, and related scientific literature. The results demonstrate the importance of strengthening regulations, transparency, and public participation so that the MBG policy is not only socially effective but also aligns with the principles of welfare and Islamic governance ethics.